The Role of Microbiological Monitoring in Ensuring Rational Antibacterial Prophylaxis and Therapy in the Neonatal Intensive Care Unit - Prof Batyrbek Aslanov; Ekaterina Yakovleva; Alexey Yakovlev; Dr Larisa Ermakova; Anna Nabieva (International Journal of Infectious Diseases)
Introduction: Infections are one of the leading causes of pediatric morbidity and mortality worldwide. The implementation of effective and safe antibacterial prophylaxis and therapy is crucial in the treatment of extremely premature neonates and those requiring intensive care. A concerning trend in recent years has been the global spread of multi-drug resistant pathogens. Consequently, the implementation and analysis of microbiological monitoring (MM) results, based on comprehensive and dynamic surveillance of pathogens isolated from patients, staff, and environment, allows to develop effective antibiotic therapy and disinfection protocols. Methods: A retrospective analysis of MM results was performed in the neonatal intensive care unit (NICU) of a university hospital (256 patients in 2023). Identification of microorganisms and determination of antimicrobial susceptibility were conducted using standard methods. Samples for microbiological investigation were collected according to a protocol approved in the hospital. Samples were taken from all patients within the first 24 hours of admission, then on the 4th day, and subsequently every 7 days. Results: The analysis determined the isolation rates of the following microorganisms: Klebsiella pneumoniae - 38.2%, Staphylococcus spp. - 16.7%, Pseudomonas aeruginosa - 11.6%, Acinetobacter spp. - 4.3%, Enterococcus spp. - 2.9%, Enterobacter spp. - 2.6%, and others. The primary pathogens of healthcare-associated infections in 2023 were identified as K. pneumoniae and P. aeruginosa. K. pneumoniae isolates were 100% sensitive to tigecycline and 82.4% to polymyxin B. Over 90% of K. pneumoniae were resistant to unprotected aminopenicillins and inhibitor-protected cephalosporins of the 3rd and 4th generations. P. aeruginosa was 100% sensitive to polymyxins and resistant to amikacin (75.9%), meropenem (70.4%), piperacillin-tazobactam (77.8%), tobramycin (72.4%), and ceftazidime (74.1%.) Based on the MM data, considering the specific pathology of neonates, their multimorbidity, colonization by nosocomial pathogens during previous hospitalizations, and medication history, local protocols for internal use were developed and implemented: “Guidelines for Antibacterial Prophylaxis and Therapy in Hospital Departments” and an “Antimicrobial Therapy Control Sheet” for clinical pharmacologists to monitor the prescription and consumption of antibacterials. Discussion: Continuous analysis of MM results has optimized initial empirical antibacterial therapy and perioperative prophylaxis for neonates and young children; reduced the average number of antibacterials prescribed for patients, which is fundamental for decreasing polypharmacy and the risk of drug interactions in NICU patients; and shortened the duration of antibacterial therapy. The effectiveness of antibacterial therapy is achieved through further adjustment based on MM results, considering the sensitivity of isolated pathogens, and selecting combined antimicrobial therapy by using medications with different antimicrobial activity. Conclusion: The implemented approaches play a significant role in combating the global burden of nosocomial pathogen resistance, ensuring effective and safe infection therapy in neonates, improving the quality of medical care, and optimizing the pharmacoeconomic performance of the medical facilities.